What's in a name? : talking about urban peripheries - Harris, Richard, 1952-; Vorms, Charlotte (Global suburbanisms., 2017)
In What's in a Name? editors Richard Harris and Charlotte Vorms have gathered together experts from around the world in order to provide a truly global framework for the study of the urban periphery.